2023
DOI: 10.3390/met13111807
|View full text |Cite
|
Sign up to set email alerts
|

Detonation Spraying of Ni-Based Composite Coatings Reinforced by High-Entropy Intermetallic Particles

Ahmad Ostovari Moghaddam,
Nataliya Shaburova,
Majid Naseri
et al.

Abstract: Ni-based composite coatings reinforced by high-entropy intermetallic compounds (HEICs) were prepared by detonation spraying (DS) on low alloy steel substrates. To this end, first (Ti-Nb)(V-Cr-Ni-Fe) and Al3(TiZrNbCrHfTa) HEIC powders were fabricated by arc melting followed by ball milling. The as-milled HEIC powders were then employed as reinforcement particles to prepare Ni-7wt.% HEIC composite coatings. The average particle size of the (Ti-Nb)(V-Cr-Ni-Fe) and Al3(TiZrNbCrHfTa) HEIC powders were 18 and 35 µm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Finally, the microhardness values of (FeNiCoCrMn)(MoCr) lie above all other coatings, indicating a narrow range of 999 HV to 1094 HV, with an average value of 1047 HV. These measured microhardness values, especially (FeNiCoCrMn)(MoCr) and (NbTaVZrHf)Al 3 , are significantly higher than Al 0.25 CoCrFeNiSi 0.6 (~550 HV) [35] and CoCrFeNiMn (~520 HV) [29] HEA coatings, as well as higher than the Ni-7 wt.% FeNiCrV-TiNb composite coating [33] fabricated by DS. Typically, fluctuations in the microhardness values measured along the cross-section of the coatings/substrate are observed, which can be ascribed to the segregation, oxidation, and the existence of distinct microstructure features in the DS coatings.…”
Section: Ds Coatingsmentioning
confidence: 81%
See 1 more Smart Citation
“…Finally, the microhardness values of (FeNiCoCrMn)(MoCr) lie above all other coatings, indicating a narrow range of 999 HV to 1094 HV, with an average value of 1047 HV. These measured microhardness values, especially (FeNiCoCrMn)(MoCr) and (NbTaVZrHf)Al 3 , are significantly higher than Al 0.25 CoCrFeNiSi 0.6 (~550 HV) [35] and CoCrFeNiMn (~520 HV) [29] HEA coatings, as well as higher than the Ni-7 wt.% FeNiCrV-TiNb composite coating [33] fabricated by DS. Typically, fluctuations in the microhardness values measured along the cross-section of the coatings/substrate are observed, which can be ascribed to the segregation, oxidation, and the existence of distinct microstructure features in the DS coatings.…”
Section: Ds Coatingsmentioning
confidence: 81%
“…Previous studies suggested that the fundamental characteristics of constituent elements such as the melting point, atomic size, electronegativity, and the enthalpy of the mixing of binary pairs are possible factors for determining elemental segregation in HE-ICs [33]. Obviously, elements with the highest melting point segregate from melt during the first stages of solidification, forming dendritic arms, while elements with a low melting point mainly remain in melt until the last stages of solidification, enriching inter-dendritic regions upon solidification.…”
Section: Microstructure Of Heicsmentioning
confidence: 99%
“…To employ OA combined with GRA to optimize the multiple objective process parameters for wire EDM of Inconel 825 material [22]. Many researchers have applied the Taguchibased GRA method to optimize the process parameters for high-speed turning operation of Inconel 718 material [23], micro EDM of SS 304 material [24], turning operations of Ti-6Al-4V alloy [25,26], turning S45C carbon steel [27], plasma arc welding of materials [28], end mill of glass fiber-reinforced polymers (GFRP) [29], and on tool-specific Caldie steel [23][24][25][27][28][29][30] to obtain the improved response results. EDM machining was carried out for EN-31 materials and optimized MRR through the GRA-based ANOVA method [31].…”
Section: Design Of Experimentsmentioning
confidence: 99%